Pin ball players, do your thing to help the Mothers For Peace
The poster reads: "Take that plug out of your mouth, the corks from your ears and the black lens from your eyes. Pin Ball Players, do your thing to help the Mothers For Peace between speedy burger and campus donuts. Flip a ball for the mothers for peace. Tommy would have done it for his mother. The family fun fair, Foothill and Santa Rosa S.L.O. Don't take the chance, you don't have to be a deaf dumb blind kid to help the mothers with their fight to protect us all from the nuclear menance at Diablo Canyon. Although, you may be if you don't. April 12th and 13th, 11.00 AM til 2.00 AM. All funds will be used to help the courageous. Mothers for peace. 1977."